Monitoring and development of junior cross-country skiers during sports high school - Kuorelahti, C. (University of Jyväskylä, 2023)
This thesis followed young athletes attending a sports high school by evaluating various monitoring methods and athlete development. An eight-week longitudinal research period was implemented to examine changes in frequent variables of athlete monitoring (e.g. submaximal tests, nocturnal heart rate variability (HRV), cortisol, orthostatic test etc.) (I), as well as validate several monitoring outcome parameters of heart rate (HR) and HRV (II). Secondly, assessment of performance related outcome changes and associations between subjective stress, sleep and performance-related tests were examined to determine which factors have the greatest influence on performance (III). Finally, a continuous one-year training period was studied to provide developmental and performance-related details that coaches and athletes may encounter (IV). A total of 37 young athletes participated in the studies. Laboratory-based performance-related measures consisted of submaximal running tests, explosive jump tests, in cremental maximal tests, and ski-specific double pole tests. A contactless ballis tocardiography (BCG)-based sleep device was used to collect nocturnal HR indices and sleep data. Training load was reported in individual training diaries.